Imperial capitals at war: A comparative perspective - Gregory, A (Taylor and Francis, 2016)
The First World War created serious challenges to the resilience of the population of the great imperial capitals of the major combatants. The effectiveness in responding to these challenges would play an important role in determining the outcome of the war itself. London was the mightiest of all the imperial capitals, overmatching the others in wealth and population just as the Empire that it ruled was the pre-eminent one. But understanding some of the commonalities of the challenges which it shared with other great capitals can help us understand the ways in which London responded to the upheaval of war.